Ζωντανοί άνθρωποι - Βάρναλης, Κώστας, 1883-1974 (Σεργιάδης τυπογρ., 1939)
Αλέξανδρος Παπαδιαμάντης -- Ιωάννης Κονδυλάκης -- Μένος Φιλήντας -- Λάμπρος Πορφύρας -- Γεράσιμος Βώκος -- Κωνσταντίνος Χρηστομάνος -- Λορέντζος Μαβίλης -- Κωνσταντίνος Καβάφης -- Ιωάννης Αρσένης -- Στέφανος Μαρτζώκης -- Δημήτριος Ταγκόπουλος -- Γιάννης Ψυχάρης -- Νικόλαος Πολίτης